Incidental germline findings during comprehensive genomic profiling of pancreatic and colorectal cancer: single-centre, molecular tumour board experience - Eid, Michal; Trizuljak, Jakub; Taslerova, Renata; Gryc, Martin; Vlazny, Jakub; Vilmanova, Sara; Jelinkova, Martina; Homolova, Alena; Tucek, Stepan; Hlavsa, Jan; Grolich, Tomas; Kala, Zdenek; et al. (Mutagenesis, 2025)
Multidisciplinary molecular tumor boards (MTB) are already well established in many comprehensive cancer centers and play an important role in the individual treatment planning for cancer patients. Comprehensive genomic profiling of tumor tissue based on next-generation sequencing is currently performed for diagnostic and mainly predictive testing. If somatic genomic variants are identified, which are suspected to be pathogenic germline variants (PGVs), MTB propose genetic counseling and germline DNA testing. Commonly used comprehensive genomic profiling approaches of tumor tissue do not include a matched germline DNA control. Therefore, the detection of PGVs could be only predicted based on the content of tumor cells (CTC) in selected tumor area (%) and variant allele frequency score (%). For conclusion, the role of a medical geneticist is essential in these cases. The overall prevalence of PGVs in patients with pancreatic ductal adenocarcinoma (PDAC) and colorectal cancer (CRC) is approximately 10%. In this single-center study, we present 37 patients with PDAC and 48 patients with CRC who were presented at MTB and tested using the large combined DNA/RNA sequencing panel. Content of tumor cells and variant allele frequency scores were evaluated in all tested patients. In case of suspicion of PGV and no previous genetic testing based on the standard guidelines, genetic counseling was recommended regardless of age, sex, and family history. In the PDAC subgroup, five patients were recommended by MTB for genetic counseling based on suspicious genetic findings. Based on a medical geneticist's decision, germline DNA sequencing was performed in four of these cases, and all of them tested positive for PGV in the following genes: ATM, ATM, BRCA1, and BRCA2. In the CRC subgroup, no PGV was confirmed in the two patients genetically tested based on the MTB recommendations. Furthermore, we present data from our center's registry of patients with PDAC and CRC who underwent genetic counseling and germline DNA testing based on the standard screening criteria. Our data confirm that comprehensive genomic profiling of tumor tissue can identify patients with hereditary forms of PDAC, who could remain unidentified by standard screening for hereditary forms of cancer.
Keywords: duktální karcinom slinivky břišní; Genetic Testing; Incidental Findings; zárodečné mutace; Gene Frequency; Male; kolorektální nádory; pancreatic cancer; genetické testování; High-Throughput Nucleotide Sequencing; somatic variants; next-generation sequencing; Carcinoma, Pancreatic Ductal; Adult; Aged; dospělí; mužské pohlaví; senioři; Genomics; Pancreatic Neoplasms; frekvence genu; senioři nad 80 let; Germ-Line Mutation; lidé; ženské pohlaví; Humans; Genetic Counseling; vysoce účinné nukleotidové sekvenování; nádory slinivky břišní; Aged, 80 and over; náhodný nález; germline variants; Colorectal Neoplasms; colorectal cancer; Female; lidé středního věku; genetické poradenství; Middle Aged; genomika